HOW GOOD IS MYGURU: THE LECTURERS’ PERCEIVED USEFULNESS AND ATTITUDE - Mohamed Nor Azhari Azman; Arasinah Kamis; Che Ghani Che Kob; Arman Shah Abdullah; Mohammad Adam Jerusalem; Kokom Komariah; Emy Budiastuti (Jurnal Cakrawala Pendidikan, 2020)
The integration of e-learning platforms in the higher education system has been around for a long time and is seen in line with the changes in Industrial Revolution 4.0 (IR4.0). Realizing this, Sultan Idris University of Education (UPSI), Malaysia has developed a Learning Management System (LMS) platform based on Technology Acceptance Model for its members to streamline learning and facilitating processes, namely MYGURU. The purpose of this study was to determine the applicability and attitude of the lecturers towards the used of MYGURU during the teaching, learning and facilitating process. Using a survey method, the study involved 734 and 248 lecturers who were selected using simple random sampling. The questionnaire was distributed by email in 2 months period. The results of this study found the mean score for MYGURU perceived usefulness and mean scores of lecturers' attitude to be at moderate level. The study of attitudes toward MYGURU used was modest, whereas the correlation test showed that there was a significant positive and moderate relationship between perceived usefulness and lecturers’ attitude. This study implies that developing a Learning Management System such as MYGURU requires continuous improvement in order to provide a better quality of higher education.